Long-Term Results of Anderson–Hynes Pyeloplasty in Children: How Long Follow-Up Is Necessary? - Reis, Leonardo Oliveira; Ikari, Osamu; Zani, Emerson Luís; Moretti, Tomás Bernardo Costa; Gugliotta, Antonio (European Journal of Pediatric Surgery, 2015)
Purpose After a successful pyeloplasty at 3 to 6 months, the question remains whether children need a long follow-up.Methods The medical charts of patients with long-term follow-up (> 5 years), who underwent dismembered pyeloplasty for uretero-pelvic junction obstruction (UPJO) from May 1998 to May 2007, excluding those with bilateral UPJO, solitary kidney, associated vesicoureteral reflux or other abnormalities, and inconclusive renogram due to poor renal function, were retrospectively reviewed. Ultrasonography, differential renal function (DRF, DMSA), and renal drainage on diuretic renography (diethylene-triamine-pentaacetate technetium-99 or DTPA-Tc99) were performed at 3 and 6 months every year. Results Complete data were available for 28 consecutive patients (28 renal unities) with 2 months to 12 years (mean age, 2.4 years) at surgery, of whom 21 (75%) were boys, 17 diagnosed prenatally (61%) and 18 unities (64.3%) were left, with median follow-up of 10.7 years. Images were graded according to the Society for Fetal Urology grading system: Grade III in 11 (49%) and grade IV in 17 (61%). All cases presented > 10% DRF (DMSA) and obstructed DTPA-Tc99. The T1/2 (the half-time of drainage) less than 20 minutes at 3 months was found in 21 cases (75%) and less than 25 minutes in 7 cases (25%). Renal function and patency were maintained during follow-up for all units with 8% maximum fluctuation of DRF. One index case (3.6%) of renal function deterioration presented DRF fluctuation > 8% at 3 months (from 23 to 32%) and progressive hydronephrosis and indeterminate DTPA at 6 months.Conclusions Satisfactory diuretic renogram at 3 to 6 months after pyeloplasty with maintained renal function and stable hydronephrosis suggests no need for further follow-up and indicates no functional loss with time. More than 8% DRF fluctuation might be a significant cutoff for further intervention aiming nephron preservation.
Keywords: uretero-pelvic junction; obstruction; late recurrence; UPJO